Assessing pollution-related effects of oil spills from ships in the Chinese Bohai Sea. Issue 1 (15th September 2016) - Liu, Xin; Guo, Mingxian; Wang, Yebao; Yu, Xiang; Guo, Jie; Tang, Cheng; Hu, Xiaoke; Wang, Chuanyuan; Li, Baoquan
Abstract: An analysis of the effects of potential oil spills will provide data in support of decisions related to improving the response to oil spills and its emergency management. We selected the Chinese Bohai Sea, especially the Bohai Strait, as our investigation region to provide an assessment of the effects of pollution from ship-related oil spills on adjacent coastal zones. Ship-related accidents are one of the major factors causing potential oil spills in this area. A three dimensional oil transport and transformation model was developed using the Estuary, Coastal, and Ocean Model. This proposed model was run 90 times and each run lasted for 15 days to simulate the spread and weathering processes of oil for each of four potential spill sites, which represented potential sites of ship collisions along heavy traffic lanes in the Bohai Sea. Ten neighboring coastal areas were also considered as target zones that potentially could receive pollutants once oil spilled in the study areas. The statistical simulations showed that spills in winter were much worse than those in summer; they resulted in very negative effects on several specific target zones coded Z7, Z8, Z9, and Z10 in this paper. In addition, sites S3 (near the Penglai city) and S4 (near the Yantai city) were the two most at-risk sites with a significantly high probability of pollution if spills occurred nearby during winter. The results thus provided practical guidelines for local oil spill prevention, as well as an emergency preparedness and response program. Highlights: Coupling oil fate simulation with statistical analysis Mapping firstly coastal impact of ship related oil spills in the Bohai Sea, China Identifying risky spill sites and highly impact for targeting coasts